Metformin attenuates the effect of Staphylococcus aureus on airway tight junctions by increasing PKCζ‐mediated phosphorylation of occludin. Issue 1 (18th November 2018) - Kalsi, Kameljit K.; Garnett, James P.; Patkee, Wishwanath; Weekes, Alexina; Dockrell, Mark E.; Baker, Emma H.; Baines, Deborah L.
Abstract: Airway epithelial tight junction (TJ) proteins form a resistive barrier to the external environment, however, during respiratory bacterial infection TJs become disrupted compromising barrier function. This promotes glucose flux/accumulation into the lumen which acts as a nutrient source for bacterial growth. Metformin used for the treatment of diabetes increases transepithelial resistance (TEER) and partially prevents the effect of bacteria but the mechanisms of action are unclear. We investigated the effect of metformin and Staphylococcus aureus on TJ proteins, zonula occludins (ZO)‐1 and occludin in human airway epithelial cells (H441). We also explored the role of AMP‐activated protein kinase (AMPK) and PKCζ in metformin‐induced effects. Pretreatment with metformin prevented the S. aureus ‐induced changes in ZO‐1 and occludin. Metformin also promoted increased abundance of full length over smaller cleaved occludin proteins. The nonspecific PKC inhibitor staurosporine reduced TEER but did not prevent the effect of metformin indicating that the pathway may involve atypical PKC isoforms. Investigation of TJ reassembly after calcium depletion showed that metformin increased TEER more rapidly and promoted the abundance and localization of occludin at the TJ. These effects were inhibited by the AMPK inhibitor, compound C and the PKCζ pseudosubstrate inhibitor (PSI). Metformin increased phosphorylation of occludin and acetyl‐coA‐carboxylase but only the former was prevented by PSI. This study demonstrates that metformin improves TJ barrier function by promoting the abundance and assembly of full length occludin at the TJ and that this process involves phosphorylation of the protein via an AMPK‐PKCζ pathway.